Pengaruh Penggunaan Multimedia terhadap Hasil Belajar Peserta Didik Kelas VIII SMPN 3 Makassar - Eka Ferawaty; Ramlawati Ramlawati; Sitti Saenab (Universitas Negeri Makassar, 2022)
This research aims to: (1) knowing the level of students science learning outcomes for grade VIII SMPN 3 Makassar who are taught using multimedia, (2) knowing the level of students science learning outcomes for grade VIII SMPN 3 Makassar who are taught using conventional media, (3) knowing whether there are differences in students science learning outcomes grade VIII SMPN 3 Makassar who are taught using multimedia and those taught using conventional media. This research is a quasi-experimental research with a Intact-Group Comparison design. The population in this study were all students of grade VIII SMPN 3 Makassar as many as 10 classes totaling 360 people, while the sample is grade VIII 1 as the experimental class totaling 21 people and grade VIII 10 as the control class totaling 21 people with the selection of samples by purposive sampling. The instrument in this study is a learning outcomes test in the form of multiple choice questions given via google form. Based on the results of statistical analysis, the t-count obtained is 1,96 and the t-table is 2.02, meaning that it can be concluded that there are differences in learning outcomes of students grade VIII SMPN 3 Makassar who are taught using multimedia and students who are taught using conventional media on the subject matter of the Blood Circulatory System.